Impact of mandatory online learning module for healthcare workers intending to decline influenza immunization: Implications for coronavirus disease 2019 (COVID-19) - Leanne M. Delaney; Victoria R. Williams; Nick Tomiczek; Lawrence Robinson; Alex Kiss; Jerome A. Leis (Cambridge University Press, 2021)
A policy mandating the completion of an online learning module for healthcare workers intending to decline influenza immunization was associated with a nearly 25% relative increase in immunization and significant reduction in healthcare-associated influenza. In the absence of mandatory vaccination, this model may help to augment severe acute respiratory coronavirus virus 2 (SARS-CoV-2) vaccine efforts.